2013
DOI: 10.4172/2157-2518.s9-002
|View full text |Cite
|
Sign up to set email alerts
|

The Roles and Molecular Mechanisms of Nestin Expression in Cancer with a Focus on Pancreatic Cancer

Abstract: Nestin is a class VI intermediate filament protein that is expressed in a variety of stem and progenitor cells, including primitive neuroepithelial cells and pancreatic exocrine progenitor cells. Nestin expression is closely associated with rapidly proliferating progenitor cells during development and repair processes, and higher nestin expression levels correlate with poor prognosis in some cancers. Nestin regulates many molecules during cell processes in both normal and neoplastic tissues, and its transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…It was also shown that nestin expression in PDAC cells is regulated by the transforming growth factor-β1/Smad pathway: nestin expression is induced in a Smad4-dependent manner and under hypoxic conditions. 75 Nestin was also detected in spheres together with CD133 and CD44, 73 and the recently isolated Panc-1 stem-like cell line demonstrated coexpression of CD133, CD44, Oct4, and nestin. 76 In contrast, no significant correlation between the CD133 and nestin expression patterns has been detected in PDAC tumor samples, 41 and nestin expression did not correlate with the clinical course of PDAC.…”
Section: Nestin As a Putative Marker Of Cscsmentioning
confidence: 93%
See 1 more Smart Citation
“…It was also shown that nestin expression in PDAC cells is regulated by the transforming growth factor-β1/Smad pathway: nestin expression is induced in a Smad4-dependent manner and under hypoxic conditions. 75 Nestin was also detected in spheres together with CD133 and CD44, 73 and the recently isolated Panc-1 stem-like cell line demonstrated coexpression of CD133, CD44, Oct4, and nestin. 76 In contrast, no significant correlation between the CD133 and nestin expression patterns has been detected in PDAC tumor samples, 41 and nestin expression did not correlate with the clinical course of PDAC.…”
Section: Nestin As a Putative Marker Of Cscsmentioning
confidence: 93%
“…72 In pancreatic ductal adenocarcinoma (PDAC), the expression of nestin as a putative marker of CSCs has recently been discussed. 73 , 74 High levels of nestin together with ALDH1A1 and ABCG2 were detected in metastatic cells from human PDAC injected into NOG mice; moreover, these cells showed typical features of CSCs such as sphere formation and tumorigenicity. Downregulation of nestin by shRNA in these cells resulted in decreased capacity of both sphere formation in vitro and metastasizing in vivo .…”
Section: Nestin As a Putative Marker Of Cscsmentioning
confidence: 98%
“…The C-terminal of Nestin serves as a bridge between microtubules and other IFs proteins including vimentin, desmin, or internexin. Nestin assists in an array of signaling cascades through mobilizing and demobilizing cytoskeletal IFs proteins which culminates in changes in cell dynamics [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are obvious candidates for being nestin effectors in this cascade and mediating the increased Sema3a sensitivity of nestin-expressing neurons. Studies on the role of nestin in cancer cells and other cell types has demonstrated the importance of nestin for migration/invasion, proliferation, and survival-which are reduced after nestin depletion by altering cell signaling pathways (Zhao et al 2014;Narita et al 2014;Liang et al 2018;Wei et al 2007;Zhang et al 2017;Yan et al 2016;Matsuda 2013). How nestin promotes higher sensitivity to low doses of Sema3a remains unknown, and future investigation will assess how phosphorylation of cdk5 substrates are affected by the presence of absence of nestin.…”
Section: Nestin As a Novel Gain Control Element In Sema3a Signalingmentioning
confidence: 99%